Development Information Website Based on ReactJS to Improve Image Smait Granada with the Agile Method - Wahyu Pinanda Ginting; Ramaulvi Muhammad Akhyar (P3M Politeknik Negeri Bengkalis, 2025)
SMAIT Granada Samarinda website continues to face issues, including an unresponsive display on both mobile and desktop devices and an inconsistent UI layout. In addition, the website's users experience discomfort due to the excessively contrasting color scheme. The objective of this development is to reimagine the website to enhance the user experience, thereby facilitating its use in terms of informative website features, updated websites, and the school's digital appearance. Through a series of stages, including planning, needs analysis, design, development, testing, and deployment, the Agile method and ReactJS technology are employed in the development process. The SMAIT Granada Samarinda website as a whole effectively passed the ISO 9126 standard test, and the PRTG tool demonstrated a 100% functional success rate with a teacher usability level of 85.8%, according to the researchers' findings. The findings indicated that the web interface is more responsive and organized on both mobile and desktop devices. It is designed to be user-friendly and includes various supplementary features, including the ability to display the names and photos of school staff, attendance features based on the school's location, a more detailed school profile, updated school news, the school's vision and mission, and a new student admissions page that is clear and user-friendly.